PENGARUH POLA ASUH ORANG TUA OTORITER TERHADAP MOTIVASI BELAJAR SISWA MTsN 4 BANDA ACEH - Muslima Muslima (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to determine the magnitude of the effect of authoritarian parenting on students' learning motivation at MTsN 4 Banda Aceh. This study uses a quantitative approach. The population of all students in class IX and a sample of 23 students, with purposive sampling method, data collection used a Likert scale. The data analysis technique used the SPSS Version.20 program. The results showed that there was an effect of authoritarian parenting on students' learning motivation at MTsN 4 Banda Aceh based on r results or person correlation of 0.654 indicating a perfect correlation interval. R count (0.654) > R table (0.413). With these results, there is an effect of authoritarian parenting on learning motivation. The results of the calculation of the coefficient of determination or R Square of authoritarian parenting contributed to the increase in learning motivation by 42.8%. This shows the magnitude of the increase in learning motivation at MTsN 4 Banda Aceh. a significant value of 0.000, compared to a significance level of 0.05 (5%) a significant value less than 0.05 (%) Based on the calculation results, the null hypothesis (Ho) is rejected and the working hypothesis (Ha) is accepted. This means that there is an influence of authoritarian parenting on Shiva's learning motivation at MTsN 4 Banda Aceh by 42.8%.